PENINGKATAN KREATIVITAS DAN MOTORIK HALUS MELALUI KEGIATAN MENEMPEL BIJI-BIJIAN PADA ANAK USIA 5-6 TAHUN - Halimah Halimah; Ainun Mutmainnah; Sitti Nurhidayah Ilyas (TEMATIK: Jurnal Pemikiran dan Penelitian Pendidikan Anak Usia Dini, 2021)
This research aims to find out the improvement of children's fine motor skills through grain sticking activities in Aisyiyah Ranting Kasi-Kasi Makassar Kindergarten. Based on the results of learning improvements using classroom action research methods implemented through cycle actions I and II through planning, implementation, observation, and reflection. This study involved students in the age group of 5-6 years as many as 18 people. Based on the results of the data analysis showed that the average value of the assessment category of learning outcomes obtained by children in cycle I and cycle II related to creativity and fine motor skills of children increased with classical learning completion 92 percent. The increase is seen from indicators of the carefulness of motion control in sticking to grains, uniqueness, and originality of form in sticking to grains.